Lipase-Catalyzed Esterification of Geraniol and Citronellol for the Synthesis of Terpenic Esters - da Silva Correa L.; Henriques R. O.; Rios J. V.; Lerin L. A.; de Oliveira D.; Furigo A. (Applied Biochemistry and Biotechnology, 2020)
This article describes the synthesis of terpenic esters derived from geraniol and citronellol (geranyl and citronellyl alkanoates) through esterification reactions catalyzed by the immobilized lipases from Thermomyces lanuginosus (Lipozyme TL IM®) and Candida antarctica (Novozym 435®). Geraniol was esterified with oleic, lauric, and stearic acids; and citronellol was esterified with oleic and stearic acids. For all the synthesized flavor esters, the best conditions were 35 °C, and the molar ratio between acid and alcohol was 1:1. Geranyl and citronellyl alkanoates reached yields between 80-100% within 4 h of reaction. For the synthesis of the citronellyl and geranyl oleate, higher yields were obtained in the absence of organic solvents. For the esters from lauric and stearic acids, using solvent was indispensable to improve the miscibility between the substrates. The reuse of Novozym 435® and Lipozyme TL IM® was performed for two more cycles after the first use, with yields higher than 60%. The results demonstrated the efficiency of the reaction catalyzed by these two commercial enzymes and the feasibility of the methodology for the production of synthetic flavor esters through enzymatic catalysis. The flavor esters synthesized were not described in the literature up to the date, giving this research an innovative feature.